Vicente Fox: Mexican President during the era of radical changes - E. S. Dabaguian (Ибероамериканские тетради, 2015)
The article presents the political portrait of Mexican president Vicente Fox who was in power in the biggest Latin-American country for six years from 2000 to 2006. The historical significance of this outstanding statesman is determined by his coming to power at the crucial point of the history of Mexico, when there ended a long monopoly of one party which was dominating in the national scene and began a peaceful and nonviolent change to the way of pluralistic democracy.